PANCASILA DAN GEREJA KATOLIK INDONESIA - Hadiwardoyo, Al. Purwa (P3TK, Sanata Dharma University, 2013)
The Indonesian Catholic Church should consider Pancasila as the code of ethics for the whole people of Indonesia, more than as an ideology like liberalism or communism. Pancasila could play an important role in the character building for the whole people of Indonesia, similar to the important role played by the Decalogue in the character building for the whole people of Israel in the Old Testament. The Indonesian Catholic Church might certainly be happy enough for the best practices of those five Indonesian core values, namely religiosity, humanity, national unity, democracy and social justice. But at the same time the Indonesian Catholic Church should be committed to giving her positive contributions to the whole people of Indonesia, especially through her continuous efforts to proclaim and to realize the Reign of God in this country